Higher Trace Elements and Lower Fatty Acids Levels in Erythrocytes as Predictors of Preeclampsia - Ruth Widhiati Raharjo Putri; Damar Prasmusinto; Noroyono Wibowo; Rima Irwinda; Yuditiya Purwosunu; Yudianto Budi Saroyo (Indonesian Biomedical Journal)
BACKGROUND: Preeclampsia is one of the common causes of maternal death in Indonesia. Many studies only focus on the diagnosis and pharmacological treatment of preeclampsia. However, predictors of preeclampsia need to be observed to add more focus on the etiology and prevention of preeclampsia. The imbalances of trace elements and fatty acids play an important role in preeclampsia. Therefore, this study was conducted to evaluate the status of trace elements and fatty acids in preeclampsia patients as predictors of preeclampsia.